Effect of Self-Eficacy and Locus of Control on Small and Medium Entertainment Small Scale - , Kholilul Kholik (International Conference of ASEAN Prespective and Policy (ICAP); Vol 1 No 1 (2018): INTERNATIONAL CONFERENCE OF ASEAN PERSPECTIVE AND POLICY (ICAP), 2018)
This study aims to analyze the effect of cell-eficacy and locus of control on the performance of small and medium scale enterprises. The problem is whether the cell-eficacy and locus of control affect the performance of small and medium scale businesses either partially or simultaneously. To test the hypothesis of small and medium scale entrepreneurs in Kecamatan Medan Perjuangan was asked to answer questionnaires about how they respond about cell-eficacy, locus of control and performance of small and medium enterprises using a sample of 58 respondents. The data obtained were analyzed using SPSS Program Version 1.6. The result of regression analysis is = 2,845 + 0,497 X1 + 0,315 X2 + ε. The results showed that cell-eficacy and locus of control have a positive and significant influence on the performance of small and medium scale enterprises in Kecamatan Medan Perjuangan.